Rule of Law with Asian Characteristics: cultural insights from the Occupy Central Movement in Hong Kong - Thomas, Jeffrey E. (Indonesian Journal of International Law, 2019)
This article uses the Occupy Central social movement in Hong Kong as a natural experiment to consider whether Asian culture influences the understanding and exercise of fundamental rights. In an earlier article, the author explored the relationship between Chinese culture and the rule of law as measured by the World Justice Project Rule of Law Index. This article relies on the earlier work but expands the analysis to consider Asian culture while at the same time focusing specifically on the fundamental rights aspect of the rule of law index. This article shows a strong correlation between lower scores for Asian countries on Individualism, as measured by the Hofstede Dimensions of Culture, and scores on fundamental rights, protection for freedom expression, and protection for freedom of association, as measured by the World Justice Project Index. This correlation is reflected by the Occupy Central movement. Although the movement was an exercise in fundamental rights, its purpose was to promote the rights of the community and the protests were carried out in a manner to reduce the impact on community rights When the movement ended, the negative consequences for the community were a significant reason, and the leaders of the movement were ultimately prosecuted for inciting a public nuisance.